THE MAN WITH MALIGNANT INSULINOMA: CHALLENGE IN MANAGEMENT - Sahardin, Siti Nurhanis; Kit, Tee Chee; Ibrahim, Sajaratul Syifaa’ (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Insulinoma is an uncommon pancreatic neoplasm that results in excessive insulin production. Excessive insulin production and recurrent hypoglycemia render it a potentially lethal condition. CASE A 41-year-old male with comorbid hypertension and dyslipidaemia presented with right upper quadrant pain for two days, altered bowel habits, decreased appetite, and weight loss. He underwent assessment to rule out malignancy. During hospitalisation, he developed recurrent asymptomatic hypoglycaemia despite the administration of dextrose infusion. He was confirmed to have endogenous hyperinsulinism, evidenced by increased blood C-peptide levels of 689 pmol/L during a hypoglycaemic episode with plasma glucose 3.0 mmol/L. Contrast-enhanced CT of the abdomen and pelvis demonstrated rim-enhancing hypodense lesions in the liver, with the largest lesion measuring 8.1 × 7.5 × 8.8 cm. There was also a hypodense lesion in the body of the pancreas measuring 0.7 × 0.8 cm. The liver biopsy revealed poorly differentiated neuroendocrine carcinoma. He was co-managed by the surgical and oncology teams. The lesion was unresectable, and he was also not a suitable candidate for arterial embolisation. He was prescribed diazoxide tablets to alleviate hypoglycaemia. Despite the regular intake of diazoxide, his hypoglycaemia worsened, finally resulting in his death. CONCLUSION Insulinoma is a neoplasm with a 10% likelihood of malignancy. Individuals with insulinoma often present with Whipple’s triad, characterised by hypoglycaemia symptoms, plasma glucose concentrations below 3.1 mmol/L, and symptom relief after ingestion of a high-glucose meal. Insulinoma is best treated with surgical excision. The main and challenging management issue in insulinoma is addressing recurrent hypoglycaemia in patients with unresectable tumours. Octreotide, a somatostatin analogue, is often used to reduce insulin production. Diazoxide, on the other hand, inhibits insulin secretion and stimulates glycogenolysis to enhance glucose release from the liver. In the end, a patient with malignant insulinoma may die from severe hypoglycaemia or metastatic malignancy.